Physical, psychosocial and dual-career loads as risk factors for injuries and illnesses in elite handball players: a 45-week prospective cohort study - Drole, Kristina; Paravlic, Armin; Steffen, Kathrin; Doupona, Mojca (Frontiers in Sports and Active Living, 2025)
IntroductionWhile training and competition load are well-documented risk factors for injury, the influence of dual-career loads, life stressors and overall load on both injury and illness remain less clear. The aim of this study was to investigate whether injury/illness occurrence is influenced by the training, competition, academic and work loads, as well as the overall load (sum of academic/work, training and competition loads) and life events in elite male handball players.MethodsIn this 45-week prospective cohort study, 189 elite male handball players weekly reported their load across training, competition, academic, and work domains. We derived an “overall load” variable as the sum of training, competition, academic and work hours. Health problems, including acute non-contact, overuse injuries and illnesses, were recorded using OSTRC-H2-SLO, while psychosocial load was assessed using the LESCA questionnaire. Multivariate logistic regression and non-parametric tests were used to identify risk factors and group differences.ResultsInjured athletes reported significantly higher training (MD = 2.6 h; p < 0.001), and overall loads (MD = 2.9 h; p = 0.042), but lower academic loads (MD = 2.5 h; p = 0.001) than non-injured athletes. Similarly, ill athletes had higher training load (MD = 1.55 h; p = 0.026) and competition loads (MD = 0.23 h; p < 0.001) but lower academic loads (MD = 2.24 h; p = 0.001). Training load emerged as a significant predictor of both injury (OR = 1.33) and illness (OR = 1.23), and competition load strongly predicted illness (OR = 37.00). Academic and work loads were not significant predictors. Higher LESCA total scores were associated with increased injury (p = 0.041) and illness risk (p = 0.017), while negative scores were associated with increased illness risk (p = 0.012).DiscussionTraining and competition loads are key modifiable risk factors for injury and illness, while dual career might serve as a protective factor. While negative life events appear to be associated with illness, the overall volume of life changes—regardless of whether they are positive or negative—emerges as a significant factor in injury risk. Our results support the development of an integrated biopsychosocial model of athlete's health, where sports- and non-sports-related loads, together with life events shape an athlete's vulnerability to injury and illness.